Application Of Simple Additive Weighting (SAW) For The Selection Of Breast Milk Pumps For Working Mothers - Novita Indriyani; Ahmad Fauzi; Andika Bayu Hasta Yanto (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2022)
Optimal breastfeeding is very important because it can save more than 800,000 lives of children under five every year. Among the many reasons why mothers do not exclusively breastfeed is that they go back to work (22.5%). Homemakers have a greater chance of exclusively breastfeeding because they spend more time with the baby, allowing them to breastfeed optimally. Based on the results of previous studies, working mothers give breast milk directly (when they are at home or resting) and give milk from milk. Using a breast pump is considered more practical, easier and saves time. The breastpump method (MPA) for exclusive breastfeeding for working mothers also does not interfere with the work process and offers flexibility in working hours. What worries women who work while breastfeeding is maintaining breast milk production during working hours. However, according to research, there is no significant difference between the effectiveness and satisfaction of breast milk production when using an electric breast pump. The use of a breast pump does not affect the amount of breast milk produced, even though an electric breast pump provides more effectiveness and satisfaction in expressing breast milk. This study aims to select the type of breast pump for working mothers to facilitate exclusive breastfeeding of the baby. The result of the calculation of SAW method resulted in a recommendation for a breast pump Moom Uung with a value of 15.67 The result of the calculation of SAW method resulting in a recommendation for a breast pump Moom Uung with a value of 15.67.